Reply to Di Nucci: why the counterexamples succeed. Issue 5 (30th April 2009) - Strong, C
Abstract : In my essay, a critique of "the best secular argument against abortion" I reconstructed and criticised two versions of Don Marquis's well-known argument against abortion. In critiquing the version I call the "essence argument", I presented counterexamples to one of the premises in that argument. In this issue of the journal, Ezio Di Nucci takes note of the fact that I used the term "valuable future" in the premise but used the term "future like ours" in the counterexamples. Because the terms are different, Di Nucci claimed that my counterexamples had no bearing on the premise and are therefore unsuccessful. The main error in Di Nucci's objection is a failure to acknowledge that Marquis uses the terms "valuable future" and "future like ours" interchangeably. For the purpose of reconstructing Marquis's argument, the term "valuable future" is to be taken in a sense that means the same as "future like ours". Once this point is recognised, Di Nucci's objection falls apart.